A Robotic Solution for the Restoration of Fresco Paintings. (11th November 2015) - Ceccarelli, Marco; Blanco-Moreno, Francisco; Carbone, Giuseppe; Roig, Pilar; Cigola, Michela; Regidor, Jose Luis
In this paper, a service robot solution is presented for the analysis, surveying and restoration of fresco paintings. The proposed design approach integrates robot design and restoration operation. It aims to merge them into a feasible solution that can be both practical and feasible for restorers. The simulation results are reported to show a successful design solution, which has been conceived with the constraints of a low-cost user-oriented design and the consideration of cultural heritage.